2004
DOI: 10.1093/hmg/ddh273
|View full text |Cite
|
Sign up to set email alerts
|

A synonymous SNP of the corneodesmosin gene leads to increased mRNA stability and demonstrates association with psoriasis across diverse ethnic groups

Abstract: Psoriasis is a chronic skin disorder with multifactorial aetiology. Genome-wide scans have provided unambiguous evidence for a major disease susceptibility locus on chromosome 6p21 (PSORS1). A minimal PSORS1 interval has been defined which encompasses three genes (HLA-C, HCR and CDSN) carrying psoriasis-associated SNPs. On the basis of this genetic evidence, we have undertaken an assessment of CDSN allele functional impact. A comparison of CDSN intragenic haplotypes showed that SNPs exclusive to disease-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
159
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(170 citation statements)
references
References 33 publications
9
159
1
1
Order By: Relevance
“…However, gene expression could be affected as a result of a structural change in the RNA due to the variant, and may lead to an alteration in processing or efficiency of translation (49). Several studies have shown evidence that synonymous mutations can affect mRNA secondary structure and result in abnormalities (31)(32)(33). In a study by Duan et al (32), the silent 957 C!T polymorphism of the human dopamine receptor D2 (DRD2) gene has been shown to alter mRNA folding, reduce mRNA stability and translation, as well as alter dopamine-induced DRD2 expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, gene expression could be affected as a result of a structural change in the RNA due to the variant, and may lead to an alteration in processing or efficiency of translation (49). Several studies have shown evidence that synonymous mutations can affect mRNA secondary structure and result in abnormalities (31)(32)(33). In a study by Duan et al (32), the silent 957 C!T polymorphism of the human dopamine receptor D2 (DRD2) gene has been shown to alter mRNA folding, reduce mRNA stability and translation, as well as alter dopamine-induced DRD2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Duan et al (32), the silent 957 C!T polymorphism of the human dopamine receptor D2 (DRD2) gene has been shown to alter mRNA folding, reduce mRNA stability and translation, as well as alter dopamine-induced DRD2 expression. In another study, Capon et al (33) compared the stability of mRNA transcribed from haplotypes from the psoriasisassociated corneodesmosin (CDSN) gene. They observed that the risk haplotype resulted in a 2-fold increase in mRNA stability compared with the neutral haplotype and was associated with the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The psoriasis-associated SNPs of CDSN could affect the function of the corresponding proteins. To date, only one study has shown that an intragenic SNP (SNP*971T), present in 3 common haplotypes associated with psoriasis in various ethnic groups, is responsible for an increased stability of the encoded mRNAs [43]. Although these results are in agreement with the known overexpression of CDSN in psoriatic lesions [15,34], they pointed a discrepancy between CDSN haplotypes at the mRNA level only.…”
Section: Cdsn and Human Diseasesmentioning
confidence: 89%
“…39 -41 Also, in the case of the corneodesmosin gene, a synonymous mutation located in an RNA stability motif led to increased stability of the RNA transcript by diminishing the transcript affinity for a 39 kDa RNAbinding protein. 42 More recently, a silent SNP in the multi-drug resistance 1 gene has been reported to change Genetic analysis of CSTA in psoriasis Y Vasilopoulos et al drug and inhibition interactions, suggesting that this synonymous polymorphism may affect co-translational folding of the protein. 43 These results, taken together, provide strong evidence that a synonymous mutation in exon 2 of the human cystatin A gene is strongly associated with psoriasis in both case-control and family-based association studies and act independently from HLA-Cw6.…”
Section: Discussionmentioning
confidence: 99%